Implementation of a simplified flow cytometric assays for minimal residual disease monitoring in childhood acute lymphoblastic leukemia - Marques, Ester Augusta Lima Vinhas (2016)
Institute of Integral Medicine Professor Fernando Figueira. Centro de Hematologia e Oncologia Pediátrica. Pediatric Oncology. Recife, PE, Brasil / Fundação Oswaldo Cruz. Instituto Aggeu Magalhães. Recife, PE, Brasil.